Determinants of employee perception on financial well-being in Putrajaya - Mokhtar, Nuradibah; Abd Rahim, Husniyah (Malaysian Consumer and Family Economics Association, 2016)
This study examines the relationship between financial stress, work environment, locus of control, financial behavior and financial well-being among public employees in Putrajaya. A survey was carried out to acquire data from 374 public employees using a self-administered online questionnaire, utilizing multistage random sampling. Results showed that financial stress (r= -0.643**, p< 0.01), work environment (r= 0.247**, p< 0.01), locus of control (r= 0.395**, p< 0.01) and financial behavior (r= 0.363**, p< 0.01) have significant relationship with financial well-being. It was discovered that respondents who were experiencing lower financial stress, have positive work environment, locus of control and financial behavior tend to have a better financial well-being. Financial stress (beta = -0.543, p< 0.01), work environment (beta = 0.080, p< 0.01), locus of control (beta = 0.132, p< 0.01) and financial behavior (beta = 0.244, p<0.01) have significant influence on respondents’ financial well-being. Based on the results, financial well-being can be enhanced through the decreased of the employees’ financial stress and increasing of their work environment, locus of control and financial behavior.